The impact of workplace relationships on nurse-reported quality of care and patient safety in the North West Province - Naledi Tlhako; Siedine Knobloch Coetzee; Olateju Jumoke Ajanaku; Erika Fourie (PLoS ONE, 2025)
Background There is a well-established relationship between the quality of workplace interactions among nurses, physicians, their managers, and nurse colleagues, and the subsequent improvement in patient outcomes. However, despite the growing body of research on this topic in developed countries, there remains a notable paucity of literature exploring these dynamics in developing countries. Aim To investigate the impact of workplace relationships on nurse-reported quality of care and patient safety. Design This study applied a cross-sectional survey design Method A multiphase sampling method was applied. Purposive sampling was used to select the province, health sector and hospitals (n = 3). All-inclusive sampling was applied to in-patient units of the selected hospitals and nursing staff in those units (n = 236). Data was collected in April 2021, using validated instruments. Results Nurse manager ability, leadership, and support was not experienced as positively contributing to the practice environment and had the most impact on quality of care and patient safety. Collegial nurse-physician relationships were experienced as contributing positively to the practice environment, and had the most impact on adverse events, namely medication errors, patient falls after admission and healthcare-associated infections. Increased exposure to COVID-19 patients resulted in more positive perceptions of nurses regarding collegial nurse-physician relationships. The most common perpetrators of workplace violence were supervisors/managers, followed by nursing colleagues. On average participants experience more personal workplace violence than physical workplace violence. Personal workplace violence had more effect on quality of care, patient safety, and adverse events than physical workplace violence. Conclusion Positive workplace relationships or collegiality, especially nurse-manager relationships, appear to have the most impact on nurse-perceived quality of care and patient safety, followed by nurse-physician relationships, and then workplace violence. Relevance to clinical practice The focus of education interventions should be on developing leadership, and recruiting and retaining relationship-focused leaders since leaders have the greatest impact on nurse-reported quality of care and patient safety.